Pengembangan Media Buku Pintar untuk Pembelajaran Bahasa Arab Kelas III MI Al-Madina Prambanan - Ihda A’yunil Khotimah; Nur Rohmi (Prodi PGMI Universitas Islam Nusantara Al-Azhaar Lubuklinggau, 2026)
One of the causes of low student engagement in learning at MI Al Madina Prambanan is the lack of variation in the learning media used, particularly in Arabic language instruction. Therefore, appropriate learning media are needed to make the learning process more enjoyable, one of which is by developing the “Smart Arabic Book” as a learning medium. This study employed a Research and Development (R&D) method using the ADDIE approach (Analysis, Design, Development, Implementation). The research subjects included media experts, material experts, teachers, and students. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study indicate that the feasibility of the Smart Arabic Book learning media was determined based on the following evaluations: media experts gave an average score of 3 with a feasibility percentage of 75%; material experts gave an average score of 3.8 with a feasibility percentage of 95%. Teacher assessments showed an average score of 3.4 with 85%, while students gave an average score of 3.26 with 81.5%. Based on these results, it can be concluded that the Smart Arabic Book learning media is considered feasible for use in Arabic language learning for third-grade students at the elementary school/madrasah level (SD/MI). Implications/limitations of the study – The result of this research is a smart book entitled “Smart Arabic Book.”